Urgensi Penegakan Hukum Pidana Terhadap Tindak Pidana Penyuludupan Bahan Bakar Minyak - Hery Surahman; Eko Riyadi; Virna Dewi (Universitas Muhammadiyah Ponorogo, 2026)
Fuel oil smuggling in the maritime area of Bangka Belitung is a complex criminal phenomenon with significant impact on the national economy. This research aims to analyze the urgency of criminal law enforcement against fuel oil smuggling crimes in the Bangka Belitung maritime region by examining the reality of law enforcement in the field and identifying challenges faced by law enforcement officers. The research method uses an empirical juridical approach with data collection techniques through literature study, in-depth interviews with law enforcement officers, and field observations. The research results show that criminal law enforcement against fuel oil smuggling in the Bangka Belitung maritime area still faces various structural and operational constraints. Field reality shows minimal coordination between agencies, limited surveillance infrastructure, and weak maritime area monitoring systems. Main challenges include the vast coverage of maritime areas, increasingly sophisticated modus operandi, limited operational budget, and lack of public awareness about the negative impacts of fuel oil smuggling. This research recommends the need for synergy between law enforcement agencies, improvement of maritime surveillance technology, and strengthening more comprehensive regulations to optimize criminal law enforcement against fuel oil smuggling crimes.